Moldova : Taking Compliance Management Further. (IMF Staff Country Reports; Country Report ;, 2012)
This report discusses implementation of the compliance risk model (CRM) by Moldova's tax department. The CRM has shown encouraging results in 2011, in terms of extra revenue. However, the assessment reports that for long-lasting impact, the model requires further improvement in taxpayer services, audit, tax fraud investigations, information technology, and the value-added tax refund system. The compliance plan for 2012 involves implementing measures within the segment of wealthy individuals.